2016
DOI: 10.1103/physreve.93.042701
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of spatially periodic patterns by dc voltage

Abstract: The effect of superposed dc and ac applied voltages on two types of spatially periodic instabilities in nematic liquid crystals, flexoelectric domains (FD) and electroconvection (EC), was studied. The onset characteristics, threshold voltages and critical wave vectors, were determined. We found that in general the superposition of driving with different time symmetries inhibits the pattern forming mechanisms for FD and EC as well. As a consequence the onset extends to much higher voltages than the individual d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…conductivity related) effects. We note here that recent studies on standard EC of calamitic nematics at combined (ac + dc) driving pointed out that adding a dc voltage may lead to unexpected increase of U c , including a suppression of pattern formation [38,39], due to dc-voltage-induced reduction of the conductivity and its anisotropy.…”
Section: High Frequency Patternsmentioning
confidence: 62%
“…conductivity related) effects. We note here that recent studies on standard EC of calamitic nematics at combined (ac + dc) driving pointed out that adding a dc voltage may lead to unexpected increase of U c , including a suppression of pattern formation [38,39], due to dc-voltage-induced reduction of the conductivity and its anisotropy.…”
Section: High Frequency Patternsmentioning
confidence: 62%
“…Some qualitative features of the pattern formation at superposed ac and dc voltages can, however, be estimated by testing the effect of varying σ ⊥ and δσ on the pattern onset voltages. Recent simulations have shown that reduction of δσ, that occurs upon increasing the dc bias voltage, results in the increase of the threshold voltage of electroconvection, independently of the frequency of the ac voltage component [2]. This offers an explanation for the experimental observations and thus resolves the mismatch with theory.…”
Section: Discussionmentioning
confidence: 77%
“…The results shown above clearly demonstrate that this assumption fails and should be given up if the applied voltage has a dc component. Therefore, if it is not done so, a mismatch between theoretical predictions and experimental observations about the onset characteristics (threshold voltage, critical wave number) of electroconvection patterns is practically unavoidable and actually has been reported for patterns induced by superposed ac and dc voltages [1][2]. A precise description of all ionic processes mentioned above and thus the understanding of the dc-voltage-induced conductivity changes would be a huge challenge for the future development of the theory of electric-field-induced pattern formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations